The Impact of Institutional Ownership and Board of Independence on Tax Planning with Audit Committee as Variable Moderation - Asvariwangi, Verni; Salman, M Zhofran Nur; Masruri, M Anwar (Universitas Ibn Khaldun Bogor, 2023)
The objectives of this study are To determine whether institutional ownership and board of commissioners independence have a positive influence on tax planning with the audit committee as the moderating variabel, for institutional ownership and board of commissioners independence have a negative effect on avoidance. This research is a quantitative research with a regression approach. The sample of this research is 150 data that is observed. This data collection method is secondary data in the form of financial statements of manufacturing companies listed on the Stock Exchange with data analysis of classical assumption test, T test and determination test. The results show that institutional ownership has an effect on tax planning, that the audit committee strengthens the influence of institutional ownership on tax planning, the independence of the board of commissioners has an effect on tax planning, the audit committee strengthens the influence of the independence of the board of commissioners on tax planning